Investigations on the three-stage gas-coupled Stirling-type pulse tube cryocooler. (April 2019) - Zha, Rui; Zhang, Tao; Li, Jiaqi; Tan, Jun; Zhao, Yongjiang; Zhao, Bangjian; Dang, Haizheng
Abstract: This paper establishes a theoretical model of the three-stage gas-coupled SPTC based on the electrical circuit analogy (ECA) model. A further improved ECA model for the three-stage arrangement is proposed to achieve the dynamic pressure and volume flow rate at any position of each stage, in which the effects of both the real gas and the dynamic temperature are considered to improve the accuracy. The temperature profiles in regenerators are studied by considering the temperature-induced enthalpy flow rate. Based on the above theoretical analyses, a gas-coupled three-stage SPTC driven by a moving-coil linear compressor is developed and tested. A no-load temperature of 4.8 K and cooling capacity of 40 mW/6 K are achieved experimentally with a total input power of 320 W, which is a considerable improvement of performance compared with the thermally-coupled three-stage SPTC counterpart developed by the same authors.